Implementation of Virtual Reality in Game Platformer - Heri Suharyadi; Dian Ahkam Sani; Mohammad Zoqi Sarwani (Inform: Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2020)
The realization of virtual reality is implemented on an application in the form of a game that will load the genre of platform games, where the genre of this game is highly respected by lovers of games on the Android platform. The hardware used to create virtual reality in this platformer game is an android device that has a gyroscope sensor, virtual reality cardboard, and computer devices. The software uses unity, blender, and Microsoft visual studio as a code editor. The making of this virtual reality game using the gyroscope sensor as full control of character movements that serve to minimize the device needed to play virtual reality games on Android to make it easier and more practical to play. The test results state that virtual reality can be implemented on Android games and the gyroscope sensor functions well as the main movement control in the game